Indian Society for Study of Pain, Cancer Pain Special Interest Group Guidelines on Pharmacological Management of Cancer Pain (Part II) - Thota, Raghu S (Indian J Palliat Care, 2020)
The Indian Society for Study of Pain (ISSP), Cancer Pain Special Interest Group (SIG) guidelines on pharmacological management of cancer pain in adults provide a structured, stepwise approach, which will help to improve the management of cancer pain and to provide the patients with a minimally acceptable quality of life. The guidelines have been developed based on the available literature and evidence, to suit the needs, patient population, and situations in India. A questionnaire, based on the key elements of each sub draft addressing certain inconclusive areas where evidence was lacking, was made available on the ISSP website and circulated by e-mail to all the ISSP and Indian Association of Palliative Care members. We recommend that analgesics for cancer pain management should follow the World Health Organization 3-step analgesic ladder appropriate for the severity of pain. The use of paracetamol and nonsteroidal anti-inflammatory drugs alone or in combination with opioids for mild-to-moderate pain should be used. For mild-to-moderate pain, weak opioids such as tramadol, tapentadol, and codeine can be given in combination with nonopioid analgesics. We recommend morphine as the opioid of the first choice for moderate-to-severe cancer pain. Sustained-release formulations can be started 12 hourly, once the effective 24 h dose with immediate-release morphine is established. Opioid switch or rotation should be considered if there is inadequate analgesia or intolerable side effects. For opioid-induced respiratory depression, μ receptor antagonists (e.g. naloxone) must be used promptly. Antidepressants and/or anticonvulsants should be used to treat neuropathic cancer pain, and the dose should be titrated according to the clinical response and side effects. External beam radiotherapy should be offered to all patients with painful metastatic bone pain. There is evidence on use of ketamine in cancer neuropathic pain, but with no beneficial effect, thus, it is not recommended.